Interviewer effects and the measurement of financial literacy - Thomas F. Crossley; Tobias Schmidt; Panagiota Tzamourani; Joachim K. Winter (University of Essex, Institute for Social and Economic Research (ISER), 2017)
In this paper we ask whether interviewers influence the answers to a standard set of survey questions on financial literacy. We study data from Germany's wealth survey, Panel on Household Finances (PHF). We have access to extensive paradata, including interviewer identifiers, background characteristics of interviewers, and measures of interviewer activity through the survey. We find that interviewer effects explain a significant fraction of the variance of the financial literacy score, and inter-interviewer correlations are notably larger for the financial literacy score than for other survey variables. We explore how accounting for interviewer effects can improve estimates of the effects of financial literacy on financial behaviours and outcomes.
Keywords: 330; financial literacy; interviewer effects; measurement error